Improving Students’ Reading in Narrative Text by using Extensive Reading at the Tenth Grade Students of Madrasah Aliyah Al-Fajar in Pekanbaru - Yeni Afriyeni (Lectura : Jurnal Pendidikan, 2018)
Extensive reading was defined such as an approach to the teaching and learninglanguage in which learners read large amount of books and lots of other materials thatare appropriate to learners’ linguistic competence (Day & Bamford, 1998). Thepurposes of this paper were to investigate how the extensive reading can develop thereading ability, especially vocabulary acquisition and reading comprehension at Tenthgrade students of Madrasah Aliyah Al-Fajar in Pekanbaru. The second purpose of thisstudy delved into the extensive reading can enhance their reading motivation as well asthe learners’ attitudes toward the extensive reading. The study addressed a mainresearch question and two sub-research questions which relate to the extensive reading:To what extent can Extensive reading technique improve the students’ reading narrativetext at second semester at Tenth grade students of Madrasah Aliyah Al-Fajar inPekanbaru. What are the factors that influence the changes of the students’ readingnarrative text at second semester at Tenth grade students of Madrasah Aliyah Al-Fajarin Pekanbaru. The participants of this study were 12 students at Tenth grade students ofMadrasah Aliyah Al-Fajar in Pekanbaru. The research instruments used in this study tocollect data were three main instruments namely Reading Tests (including Pre-ReadingTest and Post-Reading Test), Questionnaire, and Interview. The result of data analysisrevealed the significant difference. The findings suggested that teacher should helpstudents to improve their reading ability, particularly reading comprehension andvocabulary learning by engaging them in a systematic extensive reading program.